DEGRO practical guidelines for radiotherapy of breast cancer V: Therapy for locally advanced and inflammatory breast cancer, as well as local therapy in cases with synchronous distant metastases - Budach, Wilfried; Wenz, Frederik (Strahlentherapie und Onkologie, 2015)
Aim: The purpose of this work is to give practical guidelines for radiotherapy of locally advanced, inflammatory and metastatic breast cancer at first presentation. Methods: A comprehensive survey of the literature using the search phrases “locally advanced breast cancer”, “inflammatory breast cancer”, “breast cancer and synchronous metastases”, “de novo stage IV and breast cancer”, and “metastatic breast cancer” and “at first presentation” restricted to “clinical trials”, “randomized trials”, “meta-analysis”, “systematic review”, and “guideline” was performed and supplemented by using references of the respective publications. Based on the German interdisciplinary S3 guidelines, updated in 2012, this publication addresses indications, sequence to other therapies, target volumes, dose, and fractionation of radiotherapy. Results: International and national guidelines are in agreement that locally advanced, at least if regarded primarily unresectable and inflammatory breast cancer should receive neoadjuvant systemic therapy first, followed by surgery and radiotherapy. If surgery is not amenable after systemic therapy, radiotherapy is the treatment of choice followed by surgery, if possible. Surgery and radiotherapy should be administered independent of response to neoadjuvant systemic treatment. In patients with a de novo diagnosis of breast cancer with synchronous distant metastases, surgery and radiotherapy result in considerably better locoregional tumor control. An improvement in survival has not been consistently proven, but may exist in subgroups of patients. Conclusion: Radiotherapy is an important part in the treatment of locally advanced and inflammatory breast cancer that should be given to all patients regardless to the intensity and effect of neoadjuvant systemic treatment and the extent of surgery. Locoregional radiotherapy in patients with primarily distant metastatic disease should be prescribed on an individual basis.